The Derogatory Portrayal of Women in Proverbs of Esan People of Nigeria - K.I, Ehiemua; Aluede, Charles Onomudo; Aziegbe, Mabel Ejoghoye (Journal of Gender and Power, 2023)
This paper adopts interpretive and descriptive approaches in the study of derogatory Esan proverbs targeted against women in the Esan indigenous society of Nigeria. The aim is to reveal whether the content of such anti-women local proverbs in Esan are valid or anachronistic in the light of the indigenous knowledge that proverbs are ideally known to convey, and judging by cultural and modern realities. Esan people are a tribe in Edo State of Nigeria and the three researchers of this paper are native speakers of the language. We harvested Esan proverbs through our public interactions with elders, and young and old adults in both rural and urban Esan communities. Our study reveals, amongst others, that the contents of derogatory Esan proverbs with women as subjects are not valid statements, but are products of centuries of enduring patriarchal systems insensitive to cultural and modern realities evidencing the numerous virtues and accomplishments of Esan women. The paper finally affirms that the anti- women local proverbs are part of the traditional structure that has fought the success of the thoroughbred modern agitations for female empowerment and the quest for gender equality.